Lifestyle Medicine: Perspective of health needs. Review - Adrianzén-Arrieta, Gianella (2025)
Globally, the main causes of mortality and disability are associated with non-communicable chronic diseases (NCDs), and unhealthy lifestyle are a modifiable risk factor for acquiring these diseases. Adherence to a healthy lifestyle can prevent, treat, and reverse, with a lower cost and greater long-term benefit, the effects of NCDs. Lifestyle Medicine (LM) is a discipline focused on healthy lifestyle, which has been positioning itself in the reality and its introduction into undergraduate medical training, postgraduate training, and continuing medical education is already taking place mainly in the United States of America and Europe. A review of the databases PubMed/Medline, Web of Science, Scopus and Google Scholar was carried out, with the purpose of documenting a perspective of what the LM is, its effects, forms of application and recent results of its implementation in the health. LS offers a cost-benefit alternative to prevent, treat and reverse NCDs.